RETRACTED: Brassica juncea Lines with Substituted Chimeric GFP-CENH3 Give Haploid and Aneuploid Progenies on Crossing with Other Lines - Watts, Anshul; Singh, Sunil K.; Bhadouria, Jyoti; Naresh, Vasupalli; Bishoyi, Ashok K.; Geetha, K. A.; Chamola, Rohit; Pattanayak, Debasis; Bhat, Shripad R. (Frontiers in Plant Science, 2017)
Haploids and doubled haploids are invaluable for basic genetic studies and in crop improvement. A novel method of haploid induction through genetic engineering of the Centromere Histone Protein gene, CENH3, has been demonstrated in Arabidopsis. The present study was undertaken to develop haploid inducer (HI) lines of Brassica juncea based on the principles elaborated in Arabidopsis. B. juncea was found to carry three copies of CENH3 which generated five different transcripts, of which three transcripts resulted from alternative splicing. Unlike Arabidopsis thaliana where native CENH3 gene was knocked out for constructing HI lines, we used RNAi approach to knockdown the native CENH3 genes. Further, to rescue CENH3 silenced cells, a GFP-CENH3-tailswap construct having N terminal GFP fused to H3.3 tail sequences and synthetic CENH3 histone fold domain sequences was devised. A total 38 transgenic B. juncea plants were regenerated following co-transformation with both silencing and rescue cassettes and transgenics carrying either or both the constructs were obtained. Transgenic status was confirmed through PCR, Southern and qRT-PCR analyses. Co-transformed lines were crossed to untransformed B. juncea or a line expressing only GFP-tailswap. FACS and cytological analyses of progenies revealed partial or complete elimination of B. juncea chromosomes thereby giving rise to aneuploids and haploid. This is the first report in a polyploidy crop demonstrating that CENH3 engineering could be used to develop HI lines.